The Associated With Carbon Conversion Rate and Source–Sink Enzyme Activity in Tomato Fruit Subjected to Water Stress and Potassium Application - Luo, Anrong; Zhou, Chenni; Chen, Jinliang (Frontiers in Plant Science, 2021)
Carbon metabolism in higher plants is a basic physiological metabolism, and carbon allocation and conversion require the activity of various enzymes in metabolic processes that alter the content and overall composition of sugars in the sink organ. However, it is not known how various enzymes affect carbon metabolism when tomato plants are subjected to water stress or treated with potassium. Although the process of carbon metabolism is very complex, we used the carbon conversion rate to compare and analyze the enzyme activities related to sugar metabolism and find out which carbon conversion rate are the most important. Results showed that water stress and potassium increased carbon import flux in the fruit, which was beneficial to carbon accumulation. Water deficit increased the activity of sucrose synthase (SuSy) and starch phosphorylase (SP) and decreased the activity of sucrose phosphate synthase (SPS) and adenosine diphosphate glucose pyrophosphorylase (AGPase) in the source. Water stress increased the activity of acid invertase (AI), SuSy and SP but decreased the activity of AGPase in the sink. Potassium modified the balance of enzymes active in sugar and starch metabolism by increasing the activity of AI, SuSy, SPS and SP and significantly decreasing the activity of AGPase, resulting in increase of hexose. Canonical correlational analysis revealed that the carbon conversion rate was mainly affected by the relative rate of conversion of sucrose to fructose and glucose [p1(t)] and glucose to starch [p5m(t)]. SuSy and AGPase had the greatest effect on enzyme activity in the fruit; respectively regulated p1(t) and p5m(t).